Pengaruh Konten TikTok Food Vlogger di Wilayah Surabaya Terhadap Minat Kuliner Mahasiswa S1 Pendidikan Tata Boga UNESA - Mumtaza Tasynim; Andika K. Widagdo; Any Sutiadiningsih; Nurul F. Rizkiyah (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to determine the significant influence of TikTok food vlogger content in the Surabaya area on the culinary interest of undergraduate students in the Culinary Education Program at UNESA. The research employs a descriptive quantitative approach using a survey method. The sample consists of 90 respondents selected through purposive sampling. Data were analyzed using simple linear regression analysis. The results indicate a significant influence of TikTok food vlogger content in the Surabaya area on the culinary interest of students in the Culinary Education undergraduate program at UNESA.